A fresh look at ground beef spoilage - Frink, Lauren Meghann (My University, 2025)
The objective of this study was to determine the point at which ground beef reaches spoilage as determined by consumers relative to microbiological, lipid oxidation, color measurements, and the meat microbiome. Retail ground beef packages were delivered to the KSU meat laboratory from a case-ready facility and randomly assigned to a display duration (0 – 14 d). Packages were stored in mother-bags at 2 – 4°C in the absence of light until placed in coffin-style retail cases under fluorescent lighting conditions at 2 – 4°C for 8 different display periods. Consumer sensory analysis of visual, odor, touch, and taste were compared to objective measurements of trained sensory redness scores, discoloration scores, microbiological, lipid oxidation, and meat microbiome analysis. For each organoleptic measurement, consumers were asked if they would purchase the sample, and whether or not they thought the sample was spoiled. Consumers were less (P < 0.05) likely to purchase and more (P < 0.05) likely to rate samples as spoiled based on visual, touch, and odor evaluation once they reached 8 d of display. Logistic regression models were generated and indicated appearance measurements were the strongest predictors of consumers likeliness to purchase, and spoilage assessment. Threshold values of 50, 75, 90, and 95% were identified for consumer purchase intent, and values of 5, 10, 25, and 50% were identified for consumer spoilage indication. Objective measurements such as trained sensory panel redness score also served as very strong (P < 0.05) predictors, explaining 86% of the variation within the consumer purchase intent model with redness scores of 74.8, 64.1, 48.4, and 32.7 corresponding to 50, 75, 90, and 95% purchase likelihood. 77% of the variation within the consumer appearance spoilage rating model was explained by trained sensory redness score, with 74.75, 64.10, 48.40, and 32.7 corresponding to 5, 10, 25, and 50% likelihood of a consumer rating a sample as spoiled. While there are relationships present between the consumer purchase intent and spoilage rating and other quality measures, the purchase intent and spoilage decision of the consumers was mostly driven by the color and appearance of the sample in the retail case.
Keywords: Spoilage; Ground beef; Meat color; Microbial; Consumer sensory analysis